2015
DOI: 10.1097/hjh.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between left ventricular deformation and different geometric patterns according to the updated classification

Abstract: Left ventricular deformation in hypertensive patients is significantly impacted by left ventricular geometry. Concentric and dilated LVH patterns have the greatest unfavourable effect on 2DE and 3DE left ventricular mechanics. The updated classification of left ventricular geometry provides valuable and comprehensive information about left ventricular mechanical deformation and function in hypertensive population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
1
30
0
4
Order By: Relevance
“…Any factor that impoverished LV subendocardial fibers can lead to increased twist. For example, the systolic twist increases in hypertrophic cardiomyopathy or LV hypertrophy caused by aortic stenosis (16)(17)(18) . Both conditions lead to a subendocardial dysfunction, causing an increased LV twist (19) .…”
Section: Cardiac Motion and Twistmentioning
confidence: 99%
“…Any factor that impoverished LV subendocardial fibers can lead to increased twist. For example, the systolic twist increases in hypertrophic cardiomyopathy or LV hypertrophy caused by aortic stenosis (16)(17)(18) . Both conditions lead to a subendocardial dysfunction, causing an increased LV twist (19) .…”
Section: Cardiac Motion and Twistmentioning
confidence: 99%
“…Several studies have found heterogeneous systolic alterations of the left ventricle (in the longitudinal, radial, and circumferential directions) in diverse clinical settings such as diabetes, hypertension, left ventricle hypertrophy, coronary artery disease, and heart failure [4,6]. The main aim of our study was focused in the assessment of left ventricular mechanical deformation in 20 patients with systemic arterial hypertension and 21 healthy controls to establish the differences in the left ventricular mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension represents an increase in cardiac afterload and the compensatory mechanism of is the development of left ventricular concentric hypertrophy. However, unlike hypertrophy which occurs in athletes, the hypertrophy in hypertensive patients occurs with an increase of collagen tissue production, a fact that in the long term leads to left ventricular diastolic dysfunction and secondarily atrial dysfunction by increasing filling pressures predisposing to atrial fibrillation, and in advanced stages systolic dysfunction with dilatation of the cavity and the appearance of heart failure and ventricular arrhythmias [4]. In addition, hypertrophy of the ventricular wall increases the oxygen myocardial demands, which together with the increase incidence of coronary lesions favour myocardial ischemia [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations